ANTECEDENTS THAT INFLUENCE PARTICIPATORY BUDGETARY CONFIGURATION AND ITS EFFECTS ON VERTICAL INFORMATION SHARING AND MANAGERIAL PERFORMANCE - Zonatto, Vinicius Costa da Silva; Lunardi, Micheli Aparecida; Degenhart, Larissa (Advances in Scientific and Applied Accounting, 2019)
The purpose of this study was to examine the effects of budget participation in the sharing of vertical information and in the performance of controllers with budgetary responsibility in companies operating in Brazil, observing the effects of variables antecedent to the budget process, related to actions and behavior of the leader. In order to respond to the objective, a descriptive research was carried out by means of a survey and a quantitative approach to the data analysis, based on a sample of 316 respondents who perform the role of controller, manager or controllership coordinator.The theoretical relations investigated in this research were tested using the modeling technique of structural equations. The results showed a strong relationship between leadership style and incentive of budget participation. Positive, statistically significant relationship was found between encouraging participation and budget participation, as well as between budget participation and information sharing. These results reveal that the leader’s incentive for controllers to participate in the budget processes in their organizations constitutes an important antecedent for the budget participation and its consequent effects on the managerial performance. The positive influence of vertical information sharing on performance reveals that this condition is a determinant for a better managerial performance of the controllers participating in the research. It is concluded that the antecedents of budget participation, related to the leadership style and the incentive to participate, contribute to the understanding of the budget configuration adopted by the companies and its effects on the managerial performance of controllers, which is enhanced whenthe occurrence ofvertical information sharing.